KAJIAN HUKUM TERHADAP NOTARIS YANG MENJADI DOSEN PADA PROGRAM STUDI MAGISTER KENOTARIATAN - GAMALIEL PARTIGOR SIBARANI (PREMISE LAW JURNAL, 2015)
According to Law No. 2/2014 on Notarial Profession, a Notary is appointed by the Minister as a public official who has the authority to draw up authentic deeds. In its practice, some notaries also work as lecturer. There were some problems of the research: How about the advantages and the disadvantages and then How about this position and authority as the Lecturer at The Notarial Graduate School, and whether it needed a certain rule for a Notary who also worked as a Lecturer. The result, Notary who also works as lecturer has more experience. The can share knowledge, always up to date and up grade because they are motivated to learn more, and can continue their study. The disadvantages are that he cannot focus on his job as a Notary, cannot keep in touch with their clients harmoniously. When a Notary work as a lecturer, he will be categorized as an adjunct lecturer. A Notary is considered as a public official since lecturing in his side job which is the additional social scope for a Notary as a lecturer, and it not illegal. Up to now, there has not been specifically urgent in  a specific regulation. Keywords: Notary, Notary as Lecturer, Notarial Graduate School